The reproductive potential of yellowfin tuna (Thunnus albacares Bonnaterre, 1788) caught in the eastern part of the Indian Ocean - Hartaty Hety (EDP Sciences, 2021)
Knowledge of reproduction biology provides valuable information to better understanding population dynamics, including a population's resilience to fishing. The yellowfin tuna reproductive biology in the eastern Indian Ocean was studied by analyzing some essential characteristics: size at maturity, the spawning season, frequency of spawning, egg diameter, and batch fecundity. From 2018 to 2020, 206 female yellowfin tuna were sampled (23-170 cmFL). They were using histological and morphological analysis, resulting in the size at maturity (Lm50) of yellowfin tuna being 92.73 cmFL. The spawning season of yellowfin tuna occurred between September and May, spawning every 1.55 days within the spawning period. The oocytes size ranged between 27.1 – 570.5 μm, and the mean size of oocytes (mean ± standard deviation) was 189.5±129.4 μm. The mean batch fecundity was 3.1±1.7 million oocytes, and the mean relative batch was 82.4±38.4 oocytes gram-1 of GGT weight. The uncertainties in current yellowfin stock assessment models can be reduced by providing complete information on the reproductive traits in the region to achieve a sustainable fishery.